2020
DOI: 10.1111/jch.13813
|View full text |Cite
|
Sign up to set email alerts
|

Mean dietary salt intake in Nepal: A population survey with 24‐hour urine collections

Abstract: High salt (sodium chloride) intake raises blood pressure and increases the risk of developing hypertension, a major risk factor for cardiovascular disease. Little is known about salt intake in Nepal, and no study has estimated salt consumption from 24‐hour urinary sodium excretion. Participants (n = 451) were recruited from the Community‐Based Management of Non‐Communicable Diseases in Nepal (COBIN) cohort in 2018. Salt intake was estimated by analyzing 24‐hour urinary sodium excretion. Multivariate linear reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
24
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 26 publications
5
24
3
Order By: Relevance
“…The estimated mean dietary sodium intake in Thailand is comparable with the global average (3720 mg/day) 22 and is within the range reported by western countries: United States (3608 mg/day), 23 Australia (3560 mg/day), and Canada (3325 mg/d) 23‐25 . Interestingly, estimated sodium intake in Thailand was lower than in its Asian neighbors: India (3720 mg/d in Delhi and 4098 mg/day in Andhra Pradesh); South Korea (3960 mg/day); China (4349 mg/day); Nepal (5280 mg/day); and Bangladesh (6800 mg/day) 26‐30 . Whether the comparatively lower estimates found in this study reflect a recent declining trend in Thailand cannot be stated with certainty due to the lack of previous studies using 24‐hour urine collections.…”
Section: Discussionsupporting
confidence: 61%
“…The estimated mean dietary sodium intake in Thailand is comparable with the global average (3720 mg/day) 22 and is within the range reported by western countries: United States (3608 mg/day), 23 Australia (3560 mg/day), and Canada (3325 mg/d) 23‐25 . Interestingly, estimated sodium intake in Thailand was lower than in its Asian neighbors: India (3720 mg/d in Delhi and 4098 mg/day in Andhra Pradesh); South Korea (3960 mg/day); China (4349 mg/day); Nepal (5280 mg/day); and Bangladesh (6800 mg/day) 26‐30 . Whether the comparatively lower estimates found in this study reflect a recent declining trend in Thailand cannot be stated with certainty due to the lack of previous studies using 24‐hour urine collections.…”
Section: Discussionsupporting
confidence: 61%
“…This will have implications for salt intake strategies into the future. In the present study, salt intake was negatively associated with age, with a decrease of around 1.4 g/d for each 10‐year increase in age . As this is a cross‐sectional survey, it is not clear whether this is an age‐related or cohort effect.…”
contrasting
confidence: 64%
“…In the present study, salt intake was negatively associated with age, with a decrease of around 1.4 g/d for each 10-year increase in age. 8 As this is a cross-sectional survey, it is not clear whether this is an age-related or cohort effect. If young people are increasing intakes of high salt processed food more than older adults, this could impact substantially population salt intake in the future.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Epidemiological studies have reported the association between high salt intake and the risk of cardiovascular diseases [1][2][3]. High sodium or salt intake can lead to chronic comorbidities such as hypertension, heart failure, stroke, chronic kidney disease, and increase mortality [4,5].…”
Section: Introductionmentioning
confidence: 99%